Resin composition for nanoimprint, nanoimprint optical film and application
By providing a nanoimprint resin composition containing polyether (meth)acrylate oligomer and photopolymerization initiator, the problem of difficulty in completely separating existing materials during the demolding process is solved, the completeness and accuracy of nanopatterns are achieved, and the display performance of AR or VR devices is improved.
Patent Information
- Application Number
- CN202311852738.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-07-01
AI Technical Summary
The existing ultraviolet nanoimprinting materials are difficult to completely separate from the template during the demolding process, resulting in a shortening of the template life and deteriorating the refractive index of the formed optical film material, especially in the AR and VR fields, which affect the field of view.
A resin composition for nanoimprinting is provided, including 10-95% polyether (meth)acrylate oligomer, 0.5-5% photopolymerization initiator and 0-85% organic solvent, which maintains the integrity and accuracy of the nanopattern by resisting friction during the demoulding process with excellent flexibility.
During the demolding process, the resin composition can effectively resist the adhesion and friction of the mold, avoid deformation and brittle breakage of the patterns, maintain the integrity and accuracy of the nanopatterns, thereby improving the display performance of AR or VR devices.
Smart Images

Figure BDA0004641426520000071 
Figure BDA0004641426520000081 
Figure BDA0004641426520000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanoimprinting, and particularly relates to a resin composition for nanoimprinting, a nanoimprint optical film and applications thereof. Background Art
[0002] The nanoimprinting technology has broken through the problems in the process of reducing the feature size of traditional lithography, and has the characteristics of high resolution, low cost and high yield. At present, it is widely used in the fields of semiconductor manufacturing, MEMS, biochips, biomedicine, etc., and is regarded as one of the top ten technologies that have changed mankind.
[0003] According to different processing methods, nanoimprinting can be divided into nano hot embossing, ultraviolet nanoimprinting and microcontact printing. The ultraviolet nanoimprinting technology is a pattern transfer technology that cures polymers using ultraviolet light at room temperature and low pressure. Compared with hot embossing, it can obtain nano-scale patterns without high temperature and high pressure, greatly reducing the cost of the template, shortening the imprinting time, and being comparable to optical lithography in other aspects. Therefore, it is considered to be the most promising technology for integrated circuit production. For the imprinting adhesive, in order to obtain high-resolution patterns, the most critical performance is to be able to completely separate from the template when demolding to ensure that the patterns on the template are completely transferred to the imprinting adhesive, that is, the imprinting adhesive should have a small interaction force with the template; and at the same time, it should ensure that the imprinting adhesive has sufficient adhesion force with the substrate to avoid the separation of the imprinting adhesive and the substrate during demolding.
[0004] Currently, the most important ultraviolet nanoimprinting materials can be divided into three categories, namely silicone-based, pure organic-based and fluorinated organic-based. However, silicone materials have the characteristics of low surface energy, easy demolding and strong anti-etching ability. However, since they are similar to quartz templates, once they adhere to the template, it is difficult to completely remove them without damaging the template, so it has a certain impact on the template life. Fluorinated organic polymer materials have the advantage of low surface energy, but they have a deteriorating effect on the refractive index of the optical film materials formed by nanoimprinting, especially in the fields of AR and VR, which affects the field of view angle. Pure organic materials have a relatively high surface energy, are difficult to be used to manufacture high-resolution patterns, and are easy to adhere to the template. Generally speaking, the commercially available imprinting adhesives cannot well meet the requirements of these two surfaces. In view of this, the present invention provides a resin composition for nanoimprinting, a nanoimprint optical film and applications thereof. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a resin composition for nanoimprinting, a nanoimprint optical film and applications thereof. The purpose is to provide an ultraviolet nanoimprint lithography resist with good demolding property to ensure the integrity of the nano patterns after demolding.
[0006] The technical solution of the present invention to solve the above technical problems is as follows:
[0007] First aspect, a resin composition for nanoimprinting, the resin composition comprising components in the following weight percentages: 10-95% of polyether (meth)acrylate oligomer, 0.5-5% of photoinitiator, and 0-85% of organic solvent.
[0008] Furthermore, the structure of the polyether (meth)acrylate oligomer is as shown in Formula I: wherein, R3 is selected from any one of a substituted or unsubstituted C 1-20 aliphatic hydrocarbon group, a substituted or unsubstituted C 1-20 alkoxy group, a substituted or unsubstituted C 6-30 aromatic hydrocarbon group, a C 1-20 aliphatic hydrocarbon group containing an acyl group or an amide group, a C 6-30 aromatic hydrocarbon group containing an acyl group or an amide group; R1 is hydrogen or methyl; R2 is a C 1-3 linear alkyl group; m1 is any one of natural numbers from 1 to 6, n is the degree of polymerization, in the specific embodiments provided by the present invention, n takes the value of 4; when m1 is 1, R3 is selected from a propenyl group substituted with a ketone group.
[0009] Furthermore, the structure of R3 is specifically as shown in Formula II or Formula III: wherein m2 and m3 are each independently selected from any one of natural numbers from 0 to 6; * is the site of connection to the oxygen atom; R4 and R5 are each independently selected from a substituted or unsubstituted C 1-20 aliphatic hydrocarbon group, a substituted or unsubstituted C 1-20 alkoxy group, a substituted or unsubstituted C 6-30 aromatic hydrocarbon group.
[0010] Among them, when m2 and m3 are not 0, they are equal to m1.
[0011] Furthermore, the substituted or unsubstituted C 1-20 aliphatic hydrocarbon group includes any one of a hydroxyl-substituted or unsubstituted C 1-12 alkane group, a hydroxyl-substituted or unsubstituted C 1-20 cycloalkane group; the substituted or unsubstituted C 1-20 alkoxy group includes a hydroxyl-substituted or unsubstituted C 1-12 alkoxy group; the substituted or unsubstituted C 6-30 aromatic hydrocarbon group includes an alkyl radical, a hydroxyl-substituted or unsubstituted C 6-15 aromatic hydrocarbon group containing 1-2 benzene rings.
[0012] Preferably, as the C 6-15The aromatic hydrocarbon group specifically includes: benzene ring, naphthalene, anthracene, biphenyl, biphenylene, diphenylmethane, diphenylethane, diphenylpropane, where 1 to 4 hydrogens are replaced by functional groups connected thereto.
[0013] Furthermore, the cycloalkyl group of said C 1-20 includes the monocyclic hydrocarbon of C 3-8 , the bicyclic hydrocarbon of C 6-18 , or the bridged-ring hydrocarbon of C 5-20 . Preferably, the cycloalkyl group of said C 1-20 specifically includes: monocyclic hydrocarbons such as cyclobutane, cyclopentane, cyclohexane; bicyclic hydrocarbons formed by 1 to 3 of cyclobutane, cyclopentane, cyclohexane; or bridged-ring hydrocarbons formed by 1 to 3 of cyclobutane, cyclopentane, cyclohexane, where 1 to 4 hydrogens are replaced by functional groups connected thereto.
[0014] Furthermore, the resin composition further includes components with the following weight percentages: 0% - 60% of surface-modified or unmodified inorganic nanoparticles with a refractive index ≥ 1.8, and / or 2% - 20% of (meth)acrylate monomers containing aromatic hydrocarbon groups or aliphatic hydrocarbon groups.
[0015] Preferably, the surface-modified or unmodified inorganic nanoparticles are selected from oxides or sulfides of metal elements of at least one of zirconium (Zr), titanium (Ti), zinc (Zn), germanium (Ge), niobium (Nb), molybdenum (Mo), indium (In), tin (Sn), antimony (Sb), cerium (Ce), neodymium (Nd), hafnium (Hf), tantalum (Ta), bismuth (Bi). More preferably, they are oxides or sulfides of 1 to 2 metal elements. Among them, the average particle size of the inorganic nanoparticles is 10 - 50 nm.
[0016] Preferably, the (meth)acrylate monomer is a (meth)acrylate monomer containing an alkane group of C 1-12 substituted or unsubstituted by a hydroxyl group, or a (meth)acrylate monomer containing an alkoxy group of C 1-12 substituted or unsubstituted by a hydroxyl group, or a (meth)acrylate monomer containing 1 - 2 benzene ring structures substituted or unsubstituted by an alkyl group or a hydroxyl group. The (meth)acrylate monomer specifically includes: mono(meth)acrylate, di(meth)acrylate, tri(meth)acrylate, tetra(meth)acrylate, penta(meth)acrylate, or hexa(meth)acrylate.
[0017] Preferably, examples of the (meth)acrylate monomer having an aliphatic hydrocarbon group include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, cyclohexyl (meth)acrylate, ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, octanediol di(meth)acrylate, nonanediol di(meth)acrylate, decanediol di(meth)acrylate, undecanediol di(meth)acrylate, dodecanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol di(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, or a mixture formed of at least two of them, but not limited thereto.
[0018] Preferably, examples of the (meth)acrylate monomer having an aromatic hydrocarbon group include bisphenol A di(meth)acrylate, bisphenol A polyoxyethylene ether di(meth)acrylate, benzyl (meth)acrylate, 4-biphenylmethanol (meth)acrylate, [1,1'-biphenyl]-4,4'-diyl di(meth)acrylate, or a mixture formed of at least two of them, but not limited thereto.
[0019] Furthermore, the selection of the organic solvent includes, but is not limited to, one or a mixture formed of at least two of esters, alcohols, ethers, ketones, and benzenes. Specifically, they include ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, propylene glycol monobutyl ether acetate, methoxybutyl acetate, methanol, ethanol, cyclohexanol, ethylene glycol, propylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, acetone, methyl amyl ketone, methyl isopropyl ketone, methyl isopentyl ketone, diisopropyl ketone, diisobutyl ketone, methyl isobutyl ketone, cyclohexanone, toluene, and xylene.
[0020] Among the above solvents, propylene glycol monomethyl ether, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and toluene are preferred due to their excellent solubility and dispersibility in the resin composition components.
[0021] Furthermore, a polymerization initiator is used to initiate the polymerization of polymerizable compounds. A photoinitiator is selected, and specifically, any one or a combination of at least two of α-hydroxy ketone initiators, benzoin initiators, acylphosphine oxide initiators, acetophenone initiators, morpholinone initiators, naphthalimide photoinitiators, oxime ester photoinitiators, and carbazolyl photoinitiators can be chosen.
[0022] Specifically, the photoinitiator of the present invention can be selected from one of diphenyl(2,4,6-triformyl)phosphine oxide, ethyl phenyl(2,4,6-trimethylbenzoyl)phosphinate, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 1-hydroxycyclohexyl phenyl ketone, or a mixture of at least two thereof, but is not limited thereto.
[0023] Furthermore, the resin composition further includes at least one of a surfactant, an adhesion promoter, a heat stabilizer, and an antifoaming agent.
[0024] Preferably, general surfactants can be used as the surfactant. The general surfactants are usually used in photocurable resin compositions, such as silicone surfactants, fluorine surfactants, polyether-modified silicone surfactants, polyester-modified silicone surfactants, acryloyloxy-modified silicone surfactants, etc.
[0025] Preferably, general adhesion promoters can be used as the adhesion promoter. The general adhesion promoters are usually used in photocurable resin compositions, such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, 3-glycidoxypropyltrimethoxysilane, 3-epoxypropoxymethyl dimethoxysilane, 3-epoxypropoxymethyl dimethoxysilane, 3-epoxypropoxymethyl diethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyl dimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-thiolalkylpropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyl dimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyl diethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyl diethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltriethoxysilane, etc.
[0026] Second aspect: A preparation method of a resin composition for nanoimprinting, the preparation method comprising: putting the above-mentioned polyether (meth)acrylate oligomer, photoinitiator, organic solvent, surfactant, and solvent into a reaction kettle and stirring, controlling the temperature between 20°C and 50°C, filtering after stirring for a period of time, and thus obtaining the resin composition.
[0027] Third aspect: A nanoimprinted optical film, wherein the raw material of the nanoimprinted optical film is the resin composition for nanoimprinting.
[0028] Fourth aspect: A preparation method of a nanoimprinted optical film, comprising the following steps: subjecting the resin composition for nanoimprinting to pre-baking, mold imprinting, UV curing, and demolding in sequence to obtain the nanoimprinted optical film.
[0029] Fifth aspect: An application of a nanoimprinted optical film, using the nanoimprinted optical film in the preparation of optical elements of AR and / or VR display devices.
[0030] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0031] The resin composition for nanoimprinting provided by the present invention has good flexibility. When used for preparing nano-graphs, the good flexibility helps to resist the adhesion force and frictional force of the mold during the demolding process, avoid the deformation and brittle fracture of the graph, maintain the integrity and precision of the nano-graph, and applying it to the AR or VR field is beneficial to improving the display performance of AR or VR devices. Specific Embodiments
[0032] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not intended to limit the scope of the present invention. For those without specific technical or conditions indicated in the examples, the techniques or conditions described in the literature in this field are followed, or the product specifications are followed. For the reagents or instruments without indicating the manufacturer, they are all conventional products that can be purchased through regular channels.
[0033] Examples 1-14 and Comparative Examples 1-3:
[0034] The polymerizable compound polyether (meth)acrylate oligomer used in Examples 1-14 and Comparative Examples 1-3 is shown in Table 1 below:
[0035] Table 1 Polymerizable compound polyether (meth)acrylate oligomer
[0036]
[0037]
[0038]
[0039]
[0040] In Examples 1-14 and Comparative Examples 1-3, the parts by weight of the components are shown in Table 2 below:
[0041] Table 2 Component Weight Fraction Table
[0042]
[0043]
[0044]
[0045]
[0046] Prepare a numerical composition for nanoimprinting by following the preparation steps below for the components of the above Examples 1-14 and Comparative Examples 1-3, including the following steps:
[0047] S1: Put polyether (meth)acrylate oligomer, (meth)acrylate monomer containing an aromatic hydrocarbon group or an aliphatic hydrocarbon group, ZrO2, photoinitiator, surfactant, and solvent into a reaction kettle and stir. Control the temperature at 30 °C, the stirring speed at 1500 rpm, and the stirring time at 4 h to obtain a mixed material;
[0048] S2: Filter the mixed material obtained in step S1 with a filter element pore size of 0.3 μm to obtain a photocurable composition for imprinting.
[0049] Performance Testing:
[0050] Perform the following performance tests on Examples 1-14 and Comparative Examples 1-3.
[0051] 1) Thermal shrinkage rate: Coat 5 μm onto a quartz substrate using inkjet printing technology. After drying the substrate in a vacuum drying oven for 30 minutes, pre-bake it on a vacuum hot plate at 80 °C for 1 minute, and then put it into a UV curing machine to irradiate the organic-inorganic composite material at an intensity of about 2000 mJ / cm 2 to cure and prepare a film specimen. Measure the shrinkage rate using a thermal film shrinkage test instrument by heating at 150 °C for 30 min;
[0052] 2) Hardness: Test the hardness using a Shore D hardness tester;
[0053] 3) Elongation at break: Determine the elongation at break with a tensile machine.
[0054] 4) Observation and evaluation of surface state: Use an atomic force microscope to detect whether the surface structure of the pattern is complete. The test results are shown in Table 3 below:
[0055] Table 3 Test Results
[0056]
[0057]
[0058] As can be seen from Table 3 above, compared with Comparative Examples 1-3, Examples 1-14 have good heat shrinkage performance and elongation at break. Although the comparative examples have higher hardness than the examples, it can be found from the above table that when the resin compositions prepared using the resins of the comparative examples are used for nanoimprinting, the nano-graphs obtained after demolding all have the phenomenon of structural defects. The resin composition provided by the present invention resists the frictional force during the demolding process through excellent toughness, so that the nano-graphs maintain good integrity and accuracy after demolding. Applying it to the AR / VR field is beneficial to improving the display performance of AR / VR devices.
[0059] In the description of this specification, the descriptions referring to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples", etc. mean that the specific features, structures, materials, or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, without contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples.
[0060] Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those of ordinary skill in the art can make changes, modifications, substitutions, and variations to the above embodiments within the scope of the present invention.
Claims
1. A resin composition for nanoimprinting, characterized in that, The resin composition described above comprises components in the following weight percentages: 10-95% of polyether (meth)acrylate oligomer, 0.5-5% of photoinitiator, and 0-85% of organic solvent.
2. The resin composition for nanoimprinting according to claim 1, wherein The structure of the polyether (meth)acrylate oligomer is shown in Formula I: Wherein, R3 is selected from a substituted or unsubstituted C 1-20 aliphatic hydrocarbon group, a substituted or unsubstituted C 1-20 alkoxy group, a substituted or unsubstituted C 6-30 aromatic hydrocarbon group, a C containing an acyl group or an amide group 1-20 aliphatic hydrocarbon group, a C containing an acyl group or an amide group 6-30 any one of the aromatic hydrocarbon groups; R1 is hydrogen or methyl; R2 is C 1-3 linear alkyl group; m1 is any one of natural numbers from 1 to 6.
3. The resin composition for nanoimprinting according to claim 2, characterized in that, The structure of R3 is specifically shown in Formula II or Formula III as follows: wherein m2 and m3 are each independently selected from any one of the natural numbers from 0 to 6; * is the bonding site of R3 and the oxygen atom in Formula I; R4 and R5 are each independently selected from a substituted or unsubstituted C 1-20 aliphatic hydrocarbon group, a substituted or unsubstituted C 1-20 alkoxy group, or a substituted or unsubstituted C 6-30 aromatic hydrocarbon group, respectively.
4. The resin composition for nanoimprinting according to claim 3, wherein The substituted or unsubstituted C 1-20 alkyl hydrocarbon group includes a ketone group-substituted propenyl group, a hydroxy-substituted or unsubstituted C 1-12 alkyl group, a hydroxy-substituted or unsubstituted C 1-20 cycloalkyl group; any one of the substituted or unsubstituted C 1-20 alkyl ether group includes a hydroxy-substituted or unsubstituted C 1-12 alkyl ether group; the substituted or unsubstituted C 6-30 aromatic hydrocarbon group includes an alkyl radical, a hydroxy-substituted or unsubstituted C 6-15 aromatic hydrocarbon group containing 1-2 benzene rings.
5. The resin composition for nanoimprinting according to claim 4, characterized in that, The cycloalkyl group of said C 1-20 includes any one of the monocyclic hydrocarbons of C 3-8 , the bicyclic hydrocarbons of C 6-18 , and the bridged-ring hydrocarbons of C 5-20 .
6. The resin composition for nanoimprinting according to claim 1, wherein The resin composition further comprises components in the following weight percentages: 0%-60% of surface-modified or unmodified inorganic nanoparticles with a refractive index ≥1.8, and / or 2%-20% of (meth)acrylate monomer containing an aromatic hydrocarbon group or an aliphatic hydrocarbon group.
7. The resin composition for nanoimprinting according to claim 1, wherein The resin composition further comprises at least one of a surfactant, an adhesion promoter, a heat stabilizer, and an antifoaming agent.
8. A nanoimprint optical film, characterized in that, The raw material of the nanoimprinted optical film comprises the nanoimprinting resin composition according to any one of claims 1-7.
9. A method for preparing a nanoimprint optical film according to claim 8, characterized in that, It includes the following steps: subjecting the nanoimprinting resin composition to pre-baking, mold imprinting, UV curing, and demolding in sequence to obtain the nanoimprinted optical film.
10. Application of a nanoimprint optical film, characterized in that, The nanoimprinted optical film described in claim 8 is used in the preparation of optical elements for AR and / or VR display devices.